Canine-Assisted Therapy and Quality of Life in People With Alzheimer-Type Dementia: Pilot Study - Sánchez-Valdeón, Leticia; Fernández-Martínez, Elena; Loma-Ramos, Sara; López-Alonso, Ana Isabel; Bayón Darkistade, Enrique; Ladera, Valentina (Frontiers in Psychology, 2019)
Background With the aim of improving the quality of life of people with Alzheimer’s disease, primarily as regards behavioral and psychological symptoms, we implemented canine-assisted therapy in a group of people with this disease. Methods We conducted a quasi-experimental study, with a simple pre-post case series design. Participants comprised 10 Alzheimer’s day care center users presenting severe or very severe cognitive decline. The measurement instrument employed was the Quality of Life in Late-Stage Dementia (QUALID) scale. Results By the end of the therapy, 100% of participants showed an improvement in physical, behavioral, and psychological aspects. The total scores of the QUALID scale for the three different evaluation times (before the therapy and 6 and 12 months after starting) after the canine-assisted therapy intervention were smaller and less dispersed. The total score for the QUALID scale decreased significantly (p < 0.05) at 6 and 12 months after starting therapy. An analysis by item revealed that the scores of all of them fell during the course of the therapy. Discussion Our study provides evidence of the significant benefits of canine-assisted therapy for quality of life in people with Alzheimer’s disease.